Italy and its international relations: Getting real on relative positions - Costalli, S; Ruggeri, A (Italian Political Science, 2020)
What is the position of Italy in contemporary international politics? How does Italy compare with its neighbors or with the so-called great powers in terms of power? What are the most influential factors to be considered when evaluating Italian foreign policy? Contemporary international politics is multidi-mensional and multifaceted and positioning a country in the international system involves looking at various and diverse domains. These domains and trajectories have experienced substantive changes and, in turn, the role and relative position of Italy have dramatically changed. This article aims to pro-vide empirical trends in Italy’s positioning in international relations, showing the existence of some unsolved issues and the reasons for specific underlying tensions in Italian foreign policy.